2017
DOI: 10.1039/c7ra01113j
|View full text |Cite
|
Sign up to set email alerts
|

Ring-opening polymerization of ethylene carbonate: comprehensive structural elucidation by 1D & 2D-NMR techniques, and selectivity analysis

Abstract: Meticulous structural elucidation and selectivity analysis of poly(ethylene ether carbonate) by multi-dimensional NMR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…With this mobile phase composition, PEEC with molar masses ranging from 500 to 5000 g/mol eluted at the same elution volume independent of their molar mass. Although, polymer of ethylene carbonate is composed of ether linkages along with targeted carbonate linkages, the comprehensive NMR analysis showed that the polymer is not random but statistical copolymer . The successful establishment of critical conditions of the polymer endorse the NMR results.…”
Section: Resultsmentioning
confidence: 76%
See 4 more Smart Citations
“…With this mobile phase composition, PEEC with molar masses ranging from 500 to 5000 g/mol eluted at the same elution volume independent of their molar mass. Although, polymer of ethylene carbonate is composed of ether linkages along with targeted carbonate linkages, the comprehensive NMR analysis showed that the polymer is not random but statistical copolymer . The successful establishment of critical conditions of the polymer endorse the NMR results.…”
Section: Resultsmentioning
confidence: 76%
“…PEEC homopolymers were synthesized according to the procedure described in our recent publication . For synthesis of di‐ and tri‐block copolymers polyethylene glycol monomethyl ethers (MeO‐PEO) and polyethylene glycols (PEG) of varying molar masses are used as macro‐initiator, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations